2001
DOI: 10.1007/s001250051594
|View full text |Cite
|
Sign up to set email alerts
|

UKPDS 50: Risk factors for incidence and progression of retinopathy in Type II diabetes over 6 years from diagnosis

Abstract: Diabetic retinopathy is a common complication of Type II (non-insulin-dependent) diabetes mellitus and carries with it the threat of blindness. The St Vincent declaration [1] calls for intervention to lower both the incidence and prevalence of sight-threatening retinopathy. Thus, the identification and quantification of factors associated with onset and progression is essential if this is to be achieved. This paper reports the onset of new retinopathy and the progression of established retinopathy in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

69
597
11
28

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 882 publications
(705 citation statements)
references
References 12 publications
69
597
11
28
Order By: Relevance
“…In fact, one of the largest prospective studies (n=903 patients) concluded that smoking might offer Bprotectionâ gainst development and progression of retinopathy. 5 A similar signal of Bprotection^could be inferred from this study's analyses of type 2 DM patients, although it could also be argued that the analysis was underpowered.…”
supporting
confidence: 65%
“…In fact, one of the largest prospective studies (n=903 patients) concluded that smoking might offer Bprotectionâ gainst development and progression of retinopathy. 5 A similar signal of Bprotection^could be inferred from this study's analyses of type 2 DM patients, although it could also be argued that the analysis was underpowered.…”
supporting
confidence: 65%
“…Moderate alcohol consumption [21] and smoking [22] do not appear to influence the course of DR. If anything, smoking was associated with reduced progression in the UKPDS cohort [23]. According to the EURODIAB-PCS follow-up study of the original EURODIAB cohort, onset of diabetes before puberty could be independently associated with later progression to PDR [24].…”
Section: Prevalence and Risk Factorsmentioning
confidence: 94%
“…These findings are consistent with recent data on glycaemic control in older type II diabetes subjects from the United Kingdom Prospective Diabetes Study. 19 Strengths of this study include its population-based sample and stereo retinal photographic documentation of the retinopathy level, graded initially by LC and adjudicated by a retinal specialist (PM). The limitation of our study is a relatively low follow-up rate among participants with diabetes compared to an overall follow-up rate of 75% in the whole study sample.…”
Section: Discussionmentioning
confidence: 99%